Specific Teaching for Dyslexia Children in Sekolah Disleksia Cendekia Kabupaten Kudus - Sajida Laila Hanif (Departement of Mathematics Education, 2023)
Children with normal intelligence, children with memory, writing coherence, grammar comprehension confusion and other problems due to impaired brain function, including children with dyslexia. In addition, dyslexia can also lead to dysgraphia, which is difficulty writing. Children with dyslexia (who do not have dyscalculia) have difficulty with story questions that require comprehension. However, many people continue to misunderstand dyslexia and classify children with dyslexia as having special needs. Therefore, the purpose of this article is to define dyslexia, explain how a child with dyslexia is initially diagnosed, and outline the treatments used. This study examines 10 students from the Kudus Regency Academy of Dyslexia Scholars using qualitative research techniques and a case study design. Information collected through interactive observations, interview procedures and documentation.It was found that as many as 10 students in nine schools in Kudus Regency were dyslexia. However, after treatment, it took at least 3 to 6 months for changes to start to show, and the number of students who met the criteria was only 5. Conclusions include, among other things, that psychologists enforce the status of dyslexia, that each child must identify a unique problem, and that the treatment process is based on the degree of difficulty of dyslexia. Dyslexia children are children with normal intelligence who have difficulty reading.